Influence of Comorbidities and Airway Clearance on Mortality and Outcomes of Patients With Severe Bronchiectasis Exacerbations in Taiwan - Huang, Hung-Yu; Chung, Fu-Tsai; Lin, Chun-Yu; Lo, Chun-Yu; Huang, Yu-Tung; Huang, Yu-Chen; Lai, Yu-Te; Gan, Shu-Ting; Ko, Po-Chuan; Lin, Horng-Chyuan; Chung, Kian Fan; Wang, Chun-Hua (Frontiers in Medicine, 2022)
Bronchiectasis is characterized by systemic inflammation and multiple comorbidities. This study aimed to investigate the clinical outcomes based on the bronchiectasis etiology comorbidity index (BACI) score in patients hospitalized for severe bronchiectasis exacerbations. We included non-cystic fibrosis patients hospitalized for severe bronchiectasis exacerbations between January 2008 and December 2016 from the Chang Gung Research Database (CGRD) cohort. The main outcome was the 1-year mortality rate after severe exacerbations. We used the Cox regression model to assess the risk factors of 1-year mortality. Of 1,235 patients who were hospitalized for severe bronchiectasis exacerbations, 641 were in the BACI < 6 group and 594 in the BACI ≥ 6 group. The BACI ≥ 6 group had more previous exacerbations and a lower FEV1. Pseudomonas aeruginosa (19.1%) was the most common bacterium, followed by Klebsiella pneumoniae (7.5%). Overall, 11.8% of patients had respiratory failure and the hospital mortality was 3.0%. After discharge, compared to the BACI < 6 group, the BACI ≥ 6 group had a significantly higher cumulative incidence of respiratory failure and mortality in a 1-year follow-up. The risk factors for 1-year mortality in a multivariate analysis include age [hazard ratio (HR) 4.38, p = 0.01], being male (HR 4.38, p = 0.01), and systemic corticosteroid usage (HR 6.35, p = 0.001), while airway clearance therapy (ACT) (HR 0.50, p = 0.010) was associated with a lower mortality risk. An increased risk of respiratory failure and mortality in a 1-year follow-up after severe exacerbations was observed in bronchiectasis patients with multimorbidities, particularly older age patients, male patients, and patients with a history of systemic corticosteroid use. ACT could effectively improve the risk for 1-year mortality.